FINANCIAL RATIO ANALYSIS AS AN INDICATOR OF INTERNAL CONTROL IN THE SALES AND COLLECTION CYCLE OF PT WIJAYA KARYA BETON TBK - Wawan Andi Saputra; Wihartari; Nurariqa Ahmad; Noviyati Husnul Khatimah; Nurul Fitriani; Nur Suci Anggraeni (RADJA PUBLIKA, 2025)
The purpose of this study is to evaluate the effectiveness of internal control in the sales and receivables collection cycle of PT Wijaya Karya Beton Tbk from 2022 to 2024. This study uses a quantitative approach, namely financial ratio analysis. The main focus of the analysis lies in two indicators: the receivables turnover ratio and the average collection period (ACP). The results of the analysis show that the two ratios are very different, indicating that the company's internal control does not always work well. Internal control is considered effective in 2022 based on the results of the receivables turnover ratio and ACP. However, in 2023, there was a decrease in the receivables turnover ratio and an increase in ACP, but the receivables turnover ratio and ACP increased again in 2024. These findings indicate that the company's internal control has not been running optimally continuously. Therefore, it is necessary to improve credit policies, monitor overdue receivables, and use a more integrated accounting information system. This research provides theoretical benefits for management accounting studies and is also useful for companies in designing more effective receivables management strategies, so as to maintain the company's liquidity and business continuity.